Knowledge, perception and safety practices of monkeypox infection among healthcare workers in a tertiary health facility in southwest Nigeria - AbdulMumin, Ahmed K.; Adeniyi, Makinde A.; Temitayo-Oboh, Abiola O.; Abdullah, Ahmed; Ojo, Omobola Y. (International Journal Of Community Medicine And Public Health, 2023)
Background: Monkeypox is a self-limiting disease first reported in 1970 in Zaire. It is characterised with small pox like eruptions and presently there is no approved anti–viral drug yet, clinical management of human monkey pox cases is mainly by supportive treatment and symptomatic treatment. This study assessed the knowledge, perception and safety practices of monkey pox disease among healthcare workers in a tertiary facility in Southwest state, Nigeria. Methods: The study was a descriptive cross-sectional study, web-based conducted among 402 healthcare workers in a tertiary health centre in Southwestern Nigeria. The 38-item survey instrument for the quantitative study was adapted from a similar study on COVID-19 among healthcare workers. Data was analysed using SPSS software version 20.0. Level of significance was pre-determined at p value <0.05 at a confidence level of 95%. Results: Female respondents constituted 241 (60%) while 161 (40%) were males. Mean age was 35.4±6.5 years with age group 26-35 years (49.0%) being the majority. Majority, 311 (77.4%) had poor knowledge of monkeypox while 69.9% had good perception. There was statistically significant association between age (α- 0.001), work experience (α- 0.001), tribe (α- 0.001), and average monthly income (α- 0.001) with perception about monkey pox infection among the respondents. Conclusions: Monkeypox is endemic in Nigeria and the knowledge and perceptions of healthcare workers towards the disease is a critical epidemiological determinant of its transmission rate, it is therefore imperative that intensive training be targeted among all cadres of healthcare professional including non-medical workers in healthcare setting.